Espalier architecture for revolutionizing high quality guava production - Srivastava, K K; Rajan, S; Kumar, Dinesh; Pandey, G; Verma, Anil; Pandey, Shiwanand (Indian Horticulture, 2019)
Guava bears flowers on current shoots produced on mature wood laterally or terminally. In general, flowers are produced in leaf axils in 1 or 2-3 in cluster. The crop load depends on number of new shoots, hence more new shoots result in more fruiting surface area. Upright growing branches produce new laterals near tip and basal buds of such branches remain dormant because of apical dominance phenomenon. The tip of branches produce phyto-hormone called auxin which move downwards and inhibits growth and development of lateral buds. The suppressing effect of apical buds is diluted by bending the scaffold branches at 90Â° angles; such branches produce a large number of new laterals inducing more flower buds by manipulating higher C: N ratio and stimulating proline biosynthesis in bended branch. Espalier is a technique for controlling woody growth for production of fruit. In temperate climate espalier is trained like wall to reflect more sunlight. The word espalier is French, which means something to rest on shoulder earlier referred only to actual trellis on which a tree was trained to grow.